Phase-plate electron microscopy: a novel imaging tool to reveal close-to-life nano-structures - Nagayama, Kuniaki (Springer-Verlag, 2009)
After slow progress in the efforts to develop phase plates for electron microscopes, functional phase plate using thin carbon film has been reported recently. It permits collecting high-contrast images of close-to-life biological structures with cryo-fixation and without staining. This report reviews the state of the art for phase plates and what is innovated with them in biological electron microscopy. The extension of thin-film phase plates to the material-less type using electrostatic field or magnetic field is also addressed. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12551-008-0006-z) contains supplementary material, which is available to authorized users.